RESPONSE OF GROUNDNUT GENOTYPES AGAINST STEM ROT CAUSED BY SCLEROTIUM ROLFSII SACC. UNDER SICK PLOT CONDITIONS (Journal of Plant Disease Sciences, 2025)
Sclerotium rolfsii Sacc. is responsible for causing a destructive soil-borne disease known as stem rot in groundnut crops in India. The occurance of stem rot disese has increased in the last decade in Gujarat. Fifty-three different genotypes were tested for their resistance to stem rot disease under sick plot conditions with the aim to evaluate the germplasm that is resistant to the disease. Out of them, only nine varieties, namely ICGV-86564, GJG-32, ICGV-07222, Phule Vijya, GG-13, Jawan, NRCGCS-19, GAUG-1, and R-9281, exhibited tolerant responses to , with a plant mortality rates below 50.00%. Future groundnut breeding initiatives would make further use of the identified genotypes, which have an excellent probability to provide genetic resources to improve the resistance to stem rot disease.
Keywords: Disease, Groundnut, Genotypes, Sclerotium rolfsii